2020
DOI: 10.3892/ol.2020.12042
|View full text |Cite
|
Sign up to set email alerts
|

Linalool inhibits the growth of human T cell acute lymphoblastic leukemia cells with involvement of the MAPK signaling pathway

Abstract: Linalool can inhibit the malignant proliferation of numerous human malignant solid tumors, including hepatocellular carcinoma, breast cancer, small cell carcinoma and malignant melanoma. However, the role of linalool in T cell acute lymphoblastic leukaemia (T-ALL) remains unclear. In the present study, human TALL cell lines (Jurkat, H9, Molt-4 and Raji cells) and peripheral blood mononuclear cells (PBMCs) from healthy donors were treated with various concentrations of linalool (3.75, 7.50, 15.00, 30.00, 60.00 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Previous studies based on other cancer species also reveal the effect of linalool on cell signaling pathways. Studies show that linalool can inhibit glioma cells by regulating SIRT3-SOD2-ROS signaling [ 25 ]. In addition, linalool also inhibits the survival of T-ALL cells through the MAPK pathway, and JNK activation and ERK inhibition may play a functional role in the induction of apoptosis of T-ALL cells.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies based on other cancer species also reveal the effect of linalool on cell signaling pathways. Studies show that linalool can inhibit glioma cells by regulating SIRT3-SOD2-ROS signaling [ 25 ]. In addition, linalool also inhibits the survival of T-ALL cells through the MAPK pathway, and JNK activation and ERK inhibition may play a functional role in the induction of apoptosis of T-ALL cells.…”
Section: Introductionmentioning
confidence: 99%
“…were also mediated by linalool to exhibit its antitumor action [16] . Gong et al verified by morphological analysis that linalool inhibits the viability of Jurkat cells via inducing the apoptosis of leukemia cells [17] . Linalool treatment exhibited fragmentation of chromatin, bleb formation on the cell surface, cytoplasmic shrinkage, loss of cell-to-cell contact and a reduction in their density, which is representative apoptotic features.…”
Section: Resultsmentioning
confidence: 99%
“…No studies were available on the blastogenic responses of EOs in sheep in an in vitro model of inflammation. Recent research mainly reported the anti-proliferative effects of linalool, one of the main chemical active compounds in LEO [50], L. angustifolia [51], R. officinalis [52], and M. x piperita Eos [53], on different tumor-derived cell lines. Very few findings reported the effects of EOs on peripheral blood leukocytes' proliferation in humans.…”
Section: In Vitro Pbmc Proliferative Response To Mitogen Stimulation ...mentioning
confidence: 99%